A comparison of milk protein, fat, lactose, total solids and amino acid profiles of three different buffalo breeds in Guangxi, China. Issue 4 (2nd October 2018) - Zhou, Ling; Tang, Qingfeng; Wasim Iqbal, Muhammad; Xia, Zhongsheng; Huang, Feng; Li, Lili; Liang, Mingzhen; Lin, Bo; Qin, Guangsheng; Zou, Caixia
Abstract: This study compared the milk protein, fat, lactose, total solids and amino acids (AA) profiles of Murrah buffalo, Nili-Ravi buffalo and crossbreed buffalo. Buffalo milk samples of Murrah ( n = 25), Nili-Ravi ( n = 20) and Triple-crossbred ( n = 23) were collected and milk protein, fat, lactose, total solids and 17 AA profiles were determined. Milk protein and total solids contents of Murrah buffalo were higher than those of Nili-Ravi buffalo ( p < .05). The average milk protein, fat, lactose and total solids contents of all buffalo samples were 4.76, 7.31, 5.19 and 18.40 g/100 g of milk, respectively. The AA composition of all three kinds of milk samples was rich in glutamic acid (0.89–0.96 g/100 g of milk) and poor in cysteine (0.01–0.02 g/100 g of milk). Leucine, lysine, valine and isoleucine were the most prevalent essential amino acids; while glutamic acid, proline, aspartic acid and serine were the most prevalent non-essential amino acids in the three kinds of milk samples. Significant differences ( p < .05) were observed for concentrations of Lys, Ile, Leu, Phe, Cys and His, while the other 11 amino acids had no significant differences ( p > .05). Conclusively, the milk of Murrah buffalo, Nili-Ravi buffalo and crossbreed buffalo was all rich in glutamic acid while poor in cysteine contents. After crossbreeding, the milk production of Triple-crossbred buffalo was higher than the local Chinese buffalo and its milk composition was in between those of Murrah and Nili-Ravi.